Evaluation of Tele-rheumatology during the COVID-19 Pandemic in Asian Population: A Pilot Study - Amit Sandhu; Amit Agarwal; Paramvir Kaur; Meenakshi Sharma; Harnoor Sra; Manvi Singh; Nishant Jaiswal; Anil Chauhan; Anju Gupta; Meenu Singh (International Journal of Telemedicine and Applications)
Objective. Rheumatoid arthritis (RA) is a chronic autoimmune condition associated with a potential for deformities. It is one of the common conditions to seek health care. Hence, the present study was conducted to assess the telemedicine services for patients suffering from rheumatoid arthritis during the COVID-19 pandemic in an Asian Indian population. Methods. A prospective study was conducted (March 2020–June 2020) in the telemedicine department of a premier northern Indian tertiary care institution. Out of the total patients enrolled (N=7577) in telemedicine services, 122 rheumatoid arthritis patients (1.6%) were followed for 1 month to assess change in functional status by modified Health Assessment Questionnaire (mHAQ). Telephonic interviews of the enrolled patients were conducted to determine the level of understanding of advice given by consultants, barriers during the consultation, and satisfaction with teleconsultations for rheumatology clinics. Results. For the native people, language of the clinicians was the main barrier (20%) in telerheumatology. Saving of time and money was observed as beneficial factors for patients. More than three-quarters of all rheumatoid arthritis patients were ready to use teleconsultation in the near future. A similar proportion of patients were in support for the recommendation of these services to other persons. Conclusion. We report the successful use of telemedicine services in the evaluation and management of rheumatic diseases in the current COVID-19 pandemic situation.